Modelling Monthly Headline Consumer Price Index (HCPI) through Seasonal Box-Jenkins Methodology - Emerson Abraham Jackson; Abdulai Sillah; Edmund Tamuke (International Journal of Sciences, 2018)
In this empirical work, cognisance has been given to providing a review of literature on the seasonal Box- Jenkins modelling, particularly with reference to a univariate model. Seasonal pattern of Headline Consumer Price Index (HCPI) has been produced for Sierra Leone and with EVIEWS making use of best model selection of (6,0)(0,0). Data were seasonally adjusted with iteration and sufficient diagnostic test outcomes showing that forecast using Static method yielded best outcome, with Year-on-Year inflation over the three monthly period forecasted outcomes. The correlogram of the resultant series revealed very stable outcome of the results, while MAPE for the forecast evaluation revealing marginal error for the outcome, indicating that the model is quite adequate with the chosen methodology. – – Dans ce travail empirique, on a pris connaissance de la revue de la littérature sur les Modélisation de Jenkins, en particulier en référence à un modèle univarié. La tendance saisonnière de l'indice des prix à la consommation global (IPCH) a été produite pour la Sierra Leone et avec EVIEWS en utilisant le meilleur modèle de sélection (6,0) (0,0). Les données ont été corrigées des variations saisonnières avec l'itération et les résultats des tests de diagnostic suffisants montrant que les prévisions utilisant la méthode statique ont donné les meilleurs résultats, avec une inflation d'une année à l'autre sur les trois résultats mensuels prévus. Le corrélogramme de la série résultante a révélé un résultat très stable des résultats, alors que MAPE pour l'évaluation des prévisions révélait une erreur marginale pour le résultat, indiquant que le modèle est tout à fait adéquat avec la méthodologie choisie.
Additional information: This publication is based on Time Series Econometric forecasting for Inflation in Sierra Leone using Box-Jenkins methodology [ARIMA]
Keywords: C53; 330; ARIMA Model; Time Series; HCPI; Sierra Leone